A 14-Day Course of Triple Therapy is Superior to a 10-Day Course for the Eradication of Helicobacter pylori: A Canadian Study Conducted in a 'Real World' Setting. Issue 8 (2015) - Chen, Yen-I; Fallone, Carlo A
Abstract : BACKGROUND: Successful Helicobacter pylori eradication with the traditional seven-day course of proton pump inhibitor (PPI) triple therapy is declining. Prolonging therapy to either 10 or 14 days is associated with better eradications rates. OBJECTIVE: To compare the effectiveness of 14-day course of triple therapy versus a 10-day course in the treatment of H pylori in Canada . METHODS: Consecutive treatment-naive patients with clinical indications for H pylori eradication underwent either a 10-day course or a 14-day course of traditional PPI triple therapy depending on the date of the office visit (an odd date received the 10-day course, whereas an even date received the 14-day treatment). H pylori eradication was ascertained via urea breath test or gastric biopsies performed ≥4 weeks after completion of therapy. Analyses were by both intention to treat and per-protocol. RESULTS: A total of 83 patients were included in the study (31 in the 10-day group and 52 in the 14-day group). In the intention-to-treat analysis, eradication rates were 82.7% (95% CI 70% to 92%) versus 45.2% (95% CI 27% to 64%), favouring the 14-day treatment (P<0.001). Similarly, in the per-protocol analysis, eradication rates were 91.5% (95% CI 80% to 98%) versus 63.6% (95% CI 41% to 83%), favouring the 14-day arm (P=0.01). Adverse events and compliance were not significantly different between the two groups. CONCLUSION: A 14-day course of standard PPI triple therapy was superior to a shorter-duration therapy and should be included as a first-line regimen for H pylori eradication in Canada. The 10-day course of treatment did not achieve an acceptable eradication rate and should no longer be used in this country.